A Call to Resistance: The Exhortative Function of Daniel 7 - Rillera, Andrew Remington (Journal of Biblical literature, 2019)
Despite ample research on the background, composition, and redaction of Dan 7, scholarship has not adequately addressed the exhortative function of this text in its sociopolitical context. Daniel 7 contains helpful clues to the kind of "action" (Dan 11:32) that the book is encouraging its audience to pursue in response to Seleucid rule and oppression. This aspect, however, has remained underdeveloped even by scholars who have recognized how Daniel promotes a nonmilitaristic resistance to violent oppression. In contrast to Carol Newsom's claim (2017) that Dan 7 has a muted sense of resistance when compare to chapter 2, I argue that chapter 7 develops the message of chapter 2 and envisions nonviolent covenant fidelity as the proper resistance to persecution by gentile rulers. The imagery in Dan 7 pertaining to the origin and representation of the beasts and the kingdom that is applied to the humanlike figure is crucial to understanding the exhortative purpose of the vision. This purpose is brought into sharp relief when Dan 7 is juxtaposed with 1 and 2 Maccabees and the Animal Apocalypse in 1 Enoch.